Sixth annual report and accounts of the Northern Nigeria Housing Corporation : for the year ended 31 March 1967 - The Northern Nigeria Housing Corporation (Kaduna : The Northern Nigeria Housing Corporation, 1967)
This is the sixth annual report and accounts of the Northern Nigeria Housing Corporation for the year ended 31 March 1967.
lje 04/03/2019
Arch
Keywords: Housing; Low-cost Housing; Nigeria